Understory removal accelerates nucleic phosphorus release but retards residual phosphorus release in decomposing litter of Phyllostachys edulis in subtropical China. (31st March 2021) - Qiu, Lijun; Zhang, Yang; Mao, Rong; Chen, Fusheng; Liu, Juan; Yang, Guangyao; Wan, Songze
Abstract: Despite the importance of understory vegetation for ecosystem processes and functions, its contribution to the dynamics of phosphorus (P) fractions in decomposing litter has rarely been studied in subtropical plantations. Herein, by conducting an understory removal (UR) experiment in a moso bamboo ( Phyllostachys edulis ) plantation of South China, we assessed the effect of understory species on leaf litter mass loss and P fractions (inorganic P, sugar P, nucleic P, and residual P) of moso bamboo over a 12‐month incubation period. We also examined the effect of UR on soil physicochemical properties, as well as fungal and bacterial phospholipid fatty acids (PLFAs). Our results showed that UR reduced litter decomposition rate (6.0–12.4%), but exhibited no effect on total P remaining in decomposing litter. Furthermore, UR produced variable effects on the amounts of P fractions in decomposing litter. Despite no changes were observed in the amount of inorganic and sugar P fractions, UR accelerated nucleic P release (3.0–6.6%), and residual P immobilization (9.2–27.9%) in decomposing litter. Moreover, UR increased fungal PLFAs (8.0–44.9%) but decreased bacterial PLFAs (18.7–36.8%) in the soil, leading to an increase in fungal to bacterial PLFAs ratio (34.5–80.9%). The correlation analysis showed that accelerated litter nucleic P release after UR was mainly attributed to the increases in soil fungal PLFAs, while decelerated litter residual P release was mainly resulted from the increased soil fungal PLFAs and decreased soil bacterial PLFAs. These results indicate that understory vegetation can mediate the dynamics of litter P fractions via its effect on soil microbial composition in subtropical plantations and suggest that understory vegetation is crucial to maintain soil P availability in moso bamboo plantations.